IMPACT OF VARIED AMOUNTS OF NITROGENOUS FERTILIZERS ON GRAIN YIELD AND RELATED AGRO-PHYSIOLOGICAL TRAITS IN SPRING WHEAT (TRITICUM AESTIVUM L.) - FAROOQ, MR; NAZAR , MZK; AKBAR , MZ; GHAFOOR , T; SHABIR , MA; RAFIQUE , HM; QAMAR, MJ; QAZI , MA; ASLAM , Z; HAFEEZ , Z; et al. (Biological and Clinical Sciences Research Journal, 2024)
The application of nitrogen (N) is a critical factor influencing grain yield and agro-physiological traits in spring wheat (Triticum aestivum L.). This study aimed to evaluate the impact of varied nitrogen levels on grain yield and associated traits under field conditions. The study was conducted in Chak No. 136 / 6.R Haroonabad, District Bahawalnagar under the supervision of the Institute of Soil Fertility (Field) during the crop year 2022-23. A randomized complete block design (RCBD) was used, with five N treatments (160, 145, 131, 117 and 103 kg ha⁻¹) applied across three replicates. Key parameters, including flag leaf area, thousand-grain weight, spikelets per spike, number of grains per spike, chlorophyll a, stomatal conductance, net photosynthetic rate, biological yield and gain yield, were measured. The results showed a significant increase in flag leaf area, thousand-grain weight, spikelets per spike, number of grains per spike, chlorophyll a, stomatal conductance, net photosynthetic rate, biological yield and gain yield with increasing nitrogen application, with the highest yield observed at 160 kg ha⁻¹. The results unveiled the presence of highly significant variations among nitrogen treatments in wheat variety based on the agro-physiological parameters including flag leaf area, thousand-grain weight, number of spikelets per spike, number of grains per spike, chlorophyll a, stomatal conductance, net photosynthetic rate, biological yield and gain yield. Furthermore, the results also unveiled that treatments with higher nitrogen dosage produce better results for almost all the study parameters including grain yield. The correlation coefficient analysis also confirmed the results and suggested that any wheat breeding program aimed at improving wheat yield must select its parental genotypes based on traits having the highest correlation with yield i.e., flag leaf area, thousand-grain weight, number of grains per spike, chlorophyll a, stomatal conductance and net photosynthetic rate except the number of spikelets per spike and biological yield for which the correlation was positive but non-significant. The results suggest that nitrogen in higher amounts up to a certain level is necessary for obtaining maximum output from wheat crops under semi-arid conditions.